Magic: A VLSI layout system - Ousterhout, John K.; Hamachi, Gordon T.; Mayo, Robert N.; Scott, Walter S.; Taylor, George S. (Proceedings of the 21st Design Automation Conference, 1984)
Magic is a "smart" layout system for integrated circuits. The user interface is based on a new design style called logs, which combines the efficiency of mask-level design with the flexibility of symbolic design. The system incorporates expertise about design rules and connectivity directly into the layout system in order to implement powerful new operations, including: a continuous design-rule checker that operates in background to maintain an up-to-date picture of violations; an operation called plowing that permits interactive stretching and compaction; and routing tools that can work under and around existing connections in the channels. Magic uses a new data structure called corner stitching to achieve an efficient implementation of these operations.